Social and Cultural Influence on the Mushaf of the Qur'an Tadabbur Maiyah Padhangmbulan - Nisa, Ainun; Masruchin, Masruchin; Hendro, Beko (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to examine the issue of despair through the study of surah Al-Insyirah from the perspective of Mushaf Al-Qur'an Tadabbur Maiyah Padhangmbulan by Ahmad Fuad Effendi and Muhammad Ainun Nadjib which is colored by the nuances of Maiyah culture. In this case the Maiyah congregation has a role as a positive motivation and participates as a form of attention to the community without distinguishing a particular group and background. The problem of despair is a problem that is currently rife in society. So that the impact of this increasing problem of despair really requires serious community attention. Mushaf Al-Qur'an Tadabbur Maiyah Padhangmbulan offers efforts as a solution in solving various life problems, one of which is facing despair so that it can be solved and is not sustainable. This research uses a descriptive qualitative method with a literature approach to understand the relevance of this verse to social capital in Islam. The results of this study indicate that tadabbur surah Al-Insyirah can help individuals in overcoming the problem of despair, in accordance with the principles adopted by Maiyah congregations, namely facing life problems by emphasizing the importance of togetherness, empathy, and openness in addressing problems